Pengaruh Kualitas Layanan dan Harga terhadap Kepuasan Pelanggan pada Ekpedisi JNE Express Cabang Mitraserasi 034 Pondok Melati - Fiqi Akbar; Natal Indra (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This study aims to determine the Influence of Service Quality and Price on Customer Satisfaction in JNE Express Expedition MitraSerasi Branch 034 Pondok Melati. The type of research used in this study is a quantitative approach with data collection techniques using probability sanpling. The population in this study was 83 customers and was sampled using the slovin formula, which was 45 respondents The results of this study show that the service quality variable has a positive and significant influence on customer satisfaction and the price variable also has a positive and significant influence on satisfaction, this can be seen in the t value of the > t table, service quality (X1) 2,204 > 2,018 and price (X2) 2,309 > 2,018 and service quality and price simultaneously affect customer satisfaction on the JNE Express expedition Mitraserasi 034 Pondok Melati branch. This is because f calculates 16,582 > f table 3,214 and is supported by a significance value of 0.001.